Handbook of Research on Teaching the English Language Arts : Sponsored by the International Reading Association and the National Council of Teachers of English - Lapp, Diane; Fisher, Douglas (London : Routledge, 2011)
Now in its third edition, the Handbook of Research on Teaching the English Language Arts offers an integrated perspective on the teaching of the English language arts and a comprehensive overview of research in the field. Prominent scholars, researchers, and professional leaders: provide historical and theoretical perspectives about teaching the language artsfocus on bodies of research that influence decision-making within the teaching of the language artsexplore the environments for language arts teachingrefle.
Book Cover; Title; Copyright; Contents; Preface; Overview; Section I The Language Learner; Section II Contexts for Language Learning; Section III History and Theoretical Perspectives; Section IV The Many Faces of Texts; Section V Teaching the English Language Arts; Section VI Assessment of English Language Arts Teaching and Learning; Section VII Methods of Research on Teaching the English Language Arts; Contributors; Index.
English.
Print version record.
Title page of print version.
Keywords: Language arts; English language